The Effect of Providing Education Using E-Booklet Media on Changing Students' Knowledge about Prevention of Hypertension Disease at Smanu Pakis Malang District - Fitriana Dewi Wulandari; Pudji Suryani; Sugianto Hadi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Hypertension in teenagers can continue into adulthood and cause complications and even death. Providing information is one strategy that can produce behavior, namely by increasing knowledge so that it raises awareness. Providing information can be done through educational media, one of which is e-booklet. Objective: The aim of this research was to determine the level of students' knowledge about preventing hypertension before and after being given education, and the effect of providing education using e-booklet media on changes in students' knowledge about preventing hypertension at SMANU Pakis, Malang Regency. Method: This research is a quantitative research with a pre-experiment research design using a one group pretest posttest design. The population of this study was 327 students at SMANU Pakis Malang Regency with a sample size of 38 students selected using purposive sampling techniques. The instrument used was a questionnaire. Result: The research results showed that 44.7% of students' knowledge scores before being given education had sufficient knowledge with an average score of 67.63, while after being given education 73.7% of students had good knowledge with an average score of 85.92. The Wilcoxon test results show ap value of 0.000 < 0.05, meaning that Ha is accepted and there is an influence of providing education using e-booklet media on changes in students' knowledge about preventing hypertension. Conclusion: Providing education using e-booklet media can change students' previous knowledge to become good. Through providing education, it is hoped that it can broaden students' insight into taking early prevention and can be used as a basis for further research.